La Participación Ciudadana en la Formulación de la Política Pública local: el Caso de los Consejos Barriales en el Diseño del Componente Socio-cultural Plan Desarrollo en el Cantón Portoviejo 2014 – 2019 - Toala Rivas, Johnny Marcelo (2019)
This article analyzes the case of neighborhood councils as “interest groups” of citizen participation in the Portoviejo canton, Ecuador, in the update of the development plan (2014-2019). Its focus is on the approach of the mobilization theory, political and economic resources, as well as the coalitions and participatory institutions involved for this purpose. Through a normative and theoretical analysis, the limitations that prevented the participation of neighborhood councils in the design of local public policy are identified. The main results indicate that the neighborhood councils are nonexistent in the use of political resources, lack any type of financing and economic resources that allow them to participate in the design of public policies; They also did not activate the mechanisms established in the law, and finally did not generate internal or external coalitions with the different actors around the update of the development plan (2014 - 2019) of the Portoviejo canton.